Moral reasons and The moral problem - Gert Joshua (Belgrade Philosophical Annual)
When Michael Smith published The Moral Problem, he advocated only Weak Moral Rationalism: the view that moral requirements always provide us with reasons that are relevant to the rationality of our action. But in the intervening years he has changed his position. He now holds Strong Moral Rationalism: the view that moral requirements are all-things-considered rational requirements. In this paper I argue that his change in view was motivated by two things. The first is his correct view that acting as one is morally required to act is never irrational. The second is what David Copp has called The Unitary View of Reasons: the idea that there are both moral reasons for action, and non-moral ones, and both sorts count as reasons that determine what is rational to do. This combination of views pushes Smith to hold that an act counts as morally required just in case the moral reasons that favor it outweigh all other reasons, both moral and non-moral. But, I argue, there is an attractive position between Weak and Strong Moral Rationalism, which I call Moral Permissibilism. On such a view, moral requirements, while not always rational requirements (as against Strong Moral Rationalism), are always rationally permissible (as against Moral Anti-Rationalism). In order to advocate this common-sensical position, however, one must abandon the Unitary View of Reasons, and recognize that reasons of different kinds contribute to different kinds of normative verdicts.